Antimicrobial activity of Phyllanthus amarus Schumach. & Thonn and inhibition of the NorA efflux pump of Staphylococcus aureus by Phyllanthin. (May 2019) - Braga Ribeiro, Alessandra Maria; Sousa, Jonas Nascimento de; Costa, Luciana Muratori; Oliveira, Felipe Araújo de Alcântara; dos Santos, Raimunda Cardoso; Silva Nunes, Aline Suelen; da Silva, Wanderson Oliveira; Marques Cordeiro, Paulo Jorge; de Sousa Lima Neto, José; de Siqueira-Júnior, José Pinto; Kaatz, Glenn William; Barreto, Humberto Medeiros; et al.
Abstract: The aim of this study was to evaluate the antimicrobial activity of ethanoic extract of P. amarus (PAEE) and its compound Phyllanthin, as well as, investigate if these natural products could modulate the fluoroquinolone-resistance in S. aureus SA1199-B by way of overexpression of the NorA efflux pump. Microdilution tests were carried out to determine the minimal inhibitory concentration (MIC) of the PAEE or Phyllanthin against several bacterial and yeast strains. To evaluate if PAEE or Phyllanthin were able to act as modulators of the fluoroquinolone-resistance, MICs for Norfloxacin and ethidium bromide were determined in the presence or absence of PAEE or Phyllanthin against S. aureus SA1199-B. PAEE showed antimicrobial activity against Gram-negative strains, meanwhile Phyllanthin was inactive against all strains tested. Addition of PAEE or Phyllanthin, to the growth media at sub-inhibitory concentrations enhanced the activity of the Norfloxacin as well as, Ethidium Bromide, against S. aureus SA1199-B. These results indicate that Phyllanthin is able to modulate the fluoroquinolone-resistance possibly by inhibition of NorA. This hypothesis was supported by in silico docking analysis which confirmed that Phyllantin is a NorA ligand. Thus, this compound could be used as a potentiating agent of the Norfloxacin activity in the treatment of infections caused by fluoroquinolone-resistant S. aureus. Graphical abstract: Image 1 Highlights: Ethanoic extract from the aerial parts of Phyllanthus amarus (PAEE) and Phyllanthin were tested for its antimicrobial activity, as well as, for its ability to modulate the fluoroquinolone-resistance in Staphylococcus aureus SA1199-B overexpressing the efflux pump NorA. PAEE did not show antibacterial activity against Gram-positive strains, as well as Candida albicans strains tested but it was active against Gram-negative species Escherichia coli, Salmonella Typhimurium, Serratia marcescens and Pseudomonas aeruginosa with MICs ranging from 32 to 128 μg/mL tested. PAEE potentiated the activity of both Norfloxacin and Ethidium Bromide against S. aureus SA1199-B. This effect also was verified for Phyllanthin and in silico docking showed that Phyllantin is a potential NorA inhibitor. Phyllantin could be used as an adjuvant of Norfloxacin activity against fluoroquinolone-resistant S. aureus.